Education for Parents of Children with Gadget Addiction - Ina Dewi Ardiyani; Yunias Setiawati; Yi-Ting Hsieh (Jurnal Berkala Epidemiologi, 2021)
Background: Inappropriate and excessive use of gadgets can cause addiction and interfere with physical, psychological, and emotional health, increase social isolation, and negatively affect development, especially in children. The resulting impact will be greatly influenced by the role of parents, family and the environment. Purpose: This study aims to understand what education can be provided to parents of children with gadget addiction, along with how parents can choose toys and alternative games for children to reduce this gadget addiction. Methods: The design used in this article was a narrative review that involved collecting and analyzing journals using the keywords "addiction", "children", "education", "parent" and "gadget"; this obtained 10 journal articles from PubMed, two journal articles from ScienceDirect, 14 journal articles from Google Scholar published between 2015–2020, three books, and one collection of survey data from the web. Results: There were several strategies that could be applied in managing the use of gadgets by children. The authoritative type of parenting style, good parent-child relationships, parent-child attachment and family environment conditions could also affect the use of gadgets and its impact on children. Parents could additionally provide toys and alternative games suitable for the children’s age, developmental ability and safety needs. Conclusion: Parents are expected to understand how to manage children with gadget addiction and how they can choose toys and alternative games for children to reduce gadget addiction.